Isolation, production and characterization of keratinase from Bacillus sp. khayat - Khayat, Mohd Ezuan (2011)
The increase in demand of chicken meat products for human consumption has caused the accumulation of feather waste. In this research, seven local feather degrading bacteria have been isolated from soil and feather waste samples around Selangor and Johor, Malaysia. All the bacteria that obtained from the sampling procedure were then screened by incubating them in basal media that contained feathers as a carbon and nitrogen sources. Among the isolates, isolate E3 has shown the highest keratinolytic activity and feather degradation percentage compared to the others. Isolate E3 was then identified as Bacillus sp. khayat based on its 16s rRNA sequences. This strain produced keratinase optimally at a temperature of between 30 to 370C and at pH 8. The optimal tempature and pH for the bacterial growth were also found at 30 to 370C and at pH7.5 to 9 respectively. Studies using different carbon sources on keratinase production also showed that the addition of skim milk has enhanced enzyme production. The optimum concentration of skim milk for keratinase production was found at 0.2 gL-1. The concentration of feather for optimum keratinase production was determined at 1% (w/v) while for optimum growth at 0.5 to 1.5% (w/v). The bacterium was able to degrade up to 82.43% of feather in seven days with the highest keratinase production observed at the third day of incubation period. The keratinase enzyme from the bacterium was then purified through anion exchange chromatography, using DEAE cellulose as a matrix, and gel filtration chromatography, using Zorbax® column. The molecular weight analysis using SDSPAGE gel revealed that the enzyme has a molecular weight of approximately 31.62 kDa. The optimum temperature and pH of the enzyme activity were 400C and pH 8 respectively. This enzyme can also retain over 80% of its original activity for one hour when preincubated at temperatures of between 20 to 450C and at pH 6.5 to 10. In the protease inhibitor study, the enzyme was greatly inhibited by the addition of PMSF compared to other inhibitors indicating that the enzyme is a serine type protease. The enzyme was also observed to be inhibited by the presence of all tested reducing agents such as DTNB, DTT, and 2-marcaptoethanol. All of tested metal ions such as Zn2+, Hg+, Ag+, Pb2+, Mg2+, Cu+, K+, Co2+, and Ca2+ were found to give negative effect on keratinase activity. This keratinase was active against various types of proteinous subtrates either kerationous or unkeratinous proteins. However, the highest activity was observed when casein was used as the substrates, followed bysoluble keratin, BSA, egg albumin, feather, wool, and human hair. The results of this study are very importance since they can be used to raise the potential of keratinase from Bacillus sp khayat in industrial applications.